2022
DOI: 10.1002/chem.202201308
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover: How the Chalcogen Atom Size Dictates the Hydrogen‐Bond Donor Capability of Carboxamides, Thioamides, and Selenoamides (Chem. Eur. J. 31/2022)

Abstract: Thioamides and selenoamides are better hydrogen‐bond donors than carboxamides because their amino groups are more positively charged. Quantum chemical analyses reveal that this counterintuitive phenomenon, which cannot be explained by the electronegativity, originates from the larger electronic density flow from the nitrogen lone pair of the NH2 group towards the lower‐lying π* orbital on the C=S or C=Se bond. This difference can be traced back to the effective steric size of the chalcogen atoms. More informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…The orbital interaction in H-bonds follows mainly from the covalent or charge-transfer component [3,12] which arises for BTAs from the σ donor-acceptor interaction between the filled chalcogen np lone-pair type σ HOMO orbitals on one monomer and the empty σ LUMO orbitals localized on the NH 2 groups of the other monomer. ΔE oi is more stabilizing from O to S to Se as the σ HOMOs are raised in energy while the σ LUMOs are lowered in energy upon descending Group 16 (see Figure 3a and 3b and Supporting Data S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The orbital interaction in H-bonds follows mainly from the covalent or charge-transfer component [3,12] which arises for BTAs from the σ donor-acceptor interaction between the filled chalcogen np lone-pair type σ HOMO orbitals on one monomer and the empty σ LUMO orbitals localized on the NH 2 groups of the other monomer. ΔE oi is more stabilizing from O to S to Se as the σ HOMOs are raised in energy while the σ LUMOs are lowered in energy upon descending Group 16 (see Figure 3a and 3b and Supporting Data S3).…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated recently that not the electronegativity but the steric atomic size of the chalcogen in the amide bond determines the enhanced H-bond donor strength of thio-and selenoamides compared to carboxamides. [3] As the effective size of the chalcogen atom increases from O to S to Se, the amide C=X bond is elongated due to the increasing steric Pauli repulsion between the two bonded atoms for the heavier chalcogens. As a consequence, the S-3p and Se-4p atomic orbitals (AOs) have less overlap with the 2p-AO of C than the O-2p AO.…”
Section: Introductionmentioning
confidence: 99%
“…All calculations were performed by using the Amsterdam Density Functional (ADF) program developed by Baerends et al [21] based on dispersion-corrected relativistic density functional theory at the ZORA-BLYP-D3/TZP level for geometry optimizations and ZORA-BLYP-D3/TZ2P for energies. Previous works [22][23][24] have shown that this level of theory gives excellent understanding of bonding mechanism in hydrogen bonding and also in long range interactions within weakly-bound complexes. [11] Furthermore, the use of the TZP basis set for large supramolecular systems has shown to furnish accurate results.…”
Section: Methodsmentioning
confidence: 99%
“…These different hydrogen‐bonding preferences have also been observed in the crystal structures of many of their derivatives and are thought to be responsible for why certain thiourea derivatives were effective components of healable materials whereas their urea analogs were not [8, 9]. The growing interest in noncovalent interactions involving these species [10–29] has led to renewed interest in the conformational energetics of both molecules.…”
Section: Introductionmentioning
confidence: 99%
“…not [8,9]. The growing interest in noncovalent interactions involving these species [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] has led to renewed interest in the conformational energetics of both molecules.…”
mentioning
confidence: 99%